Odpowiedzi

Najlepsza Odpowiedź!
2009-10-22T22:25:16+02:00
2a² + 2ab -2ac
-5x +5y -5z
1 + 4a + 3a²
12n -8p + 6p*n - 2n = 10n - 8p +6p*n
2a² -3a - 2


Ja tę kropkę potraktowałem jako mnożenie!
  • Użytkownik Zadane
2009-10-22T22:28:34+02:00
2a(a+b-c)=2a*a+2a*b-2a*c=2a²+2ab-2ac
(x-y+z)*(-5)=-5*x+5*y-5*z=-5x+5y-5z
(3+12a+9a²) :3=3:3+12a:3+9a²:3=1+4a+3a²
4(3n-2p)+(3p-1)* 2n=4*3n-4*2p+3p*2n-1*2n=12n-8p+6np-2n=10n-8p+6np
(2a-3)*a-2=2a*a-3*a-2=2a²-3a-2
lub (2a-3)+a-2=2a-3+a-2=3a-5 lub (2a-3)-a-2=2a-3-a-2=a-5 nie wiem co jest między nawiasem a literką a :)

*mnożenie
2009-10-22T22:28:35+02:00
2a(a+b-c) = 2a(2) + 2ab - 2ac
(x-y+z) . (-5) = -5x + 5y - 5z
(3+12a+9a(2)) :3 = 1 + 4a + 3a(2)
4(3n-2p)+(3p-1). 2n = 12n - 8n +6p - 2n= 2n + 6p
(2a-3) a-2 = 2a(2) - 3a - 2